Sobre la Posición sistemática de Brunellia Ruiz & Pavon - Orozco Clara Inés (Caldasia)
Under the concept that Brunellia belongs to the Cunoniaceae rather thant being separated in Brunelliaceae, this paper examines the systematic position of Brunellia by studying the phylogentic relationships of this taxon with eleven ingrow taxa representing Cunoniaceae and using twenty characters. A total of twelve taxa represent the ingroup. The Hennig86 program based on parsimony was used to choose the hypotheses about relationships. The data of the internal group was analyzed first with four outgroups: Connarus, Davidsonia, Fothergilla y Quercus, then excluding Quercus and last with each of the outgroups independently. Data were polarized for the last analysis. Results showed that Brunellia does not belong to Cunoniaceae and Cunoniaceae is not a monophyletic group. I propose that Brunellia, and Spiraeanthemun-Acsmithia under a different family from Cunoniaceae. More research is necessary to corroborate the relationships of these taxa. The monophylyot the Cunoniaceae is also doubtful because some of its genera are nested with Davidsonia. The results also confirmed the relationships between the Rosidae and the lower Hamameliidae. Discussion about plesiomorphic and apomorphic states conditions are given for the Rosidae. The monophyly of none of Engler's tribes is confirmed. Bajo el concepto de que Brunellia es un táxon de Cunoniaceae y no una familia monogenérica Brunelliaceae, el presente trabajo examina la posición sistemática de Brunellia analizando las relaciones filogenéticas de este taxón con once taxones que representan a Cunoniaceae, con 20 caracteres morfológicos. Un total de doce taxones hacen parte del grupo interno. El programa Hennig86 basado en el método de simplicidad (parsimony) fue usado para la elección de las hipótesis de relaciones. Los datos del grupo interno fueron analizados primero con cuatro grupos externos: Connarus, Fothergilla, Davidsonia y Quercus,- con tres excluyendo a Quercusy con cada uno de ellos por separado; para este último caso los caracteres fueron polarizados. Los resultados muestran a Brunellia como taxón diferente de Cunoniaceae y a Cunoniaceae como grupo no monofilético. Se propone en este trabajo la inclusión de Brunellia, Spiraeanthemum- Acsmithia bajo una familia diferente de Cunoniaceae. Mayor investigación es necesaria para corroborar la hipótesis de relaciones de estos taxones. Se cuestiona también la monofilia de Cunoniaceae por la presencia de Davidsonia dentro del grupo interno. Se confirma la relación estrecha entre las Rosidae basales con las Hamameliidae inferiores. La apomortla y pleslomorfta de algunos caracteres es discutida. La monofilia de ninguna de las tribus de Engler es confirmada.